2% Ganciclovir Eye Drops Control Posner-Schlossman Syndrome Relapses With/Without Cytomegalovirus Intraocular Reactivation - Sheng, Qilian; Zhai, Ruyi; Fan, Xintong; Kong, Xiangmei (Frontiers in Medicine, 2022)
Background To observe and compare the efficacy of 2% ganciclovir eye drops in the treatment of Posner-Schlossman Syndrome relapses with/without cytomegalovirus intraocular reactivation. Methods A prospective cohort study enrolling 101 patients diagnosed unilateral Posner-Schlossman Syndrome in Eye & ENT hospital, Fudan University, Shanghai, China. Thorough ophthalmic examinations were given. Aqueous humor sample was collected from the attacked eye of each patient and all pathogen immunoglobulins tests were performed. All patients were treated with appropriate corticosteroids and intraocular pressure-lowering drugs. 2% ganciclovir eye drops were given to patients whose cytomegalovirus antibody aqueous humor/serum correction ratio > 0. Patients were followed up for 2 months. Ocular manifestations and cumulative drug dose were recorded. Results A cytomegalovirus ratio > 0.40 was considered cytomegalovirus reactivation. The reactivation group (N=46) had significantly higher percent of iris depigmentation (78.26%, P<.05) and endothelial cell loss rate (19.46%, P<.001) than the latent group (N=55, 58.18% and 10.86% respectively). The cumulative treatment time and 2% ganciclovir doses were 6.50±4.67 weeks and 181.70±130.95 drops for the reactivation group; 5.95±4.11 weeks and 161.89±110.66 drops for the latent group (P>.05). The median cumulative 2% ganciclovir estimated for inflammation control were 252.00±50.71 and 224.00±32.45 drops for the reactivation and latent group. The residual rate of uncontrolled cases was 0.19±0.15 and 0.00 respectively (P<.05). Conclusions A treatment course of 8-9 weeks’ 2% ganciclovir is recommended to relapses both with and without cytomegalovirus intraocular reactivation. Preventive ganciclovir application may benefit patients with historical cytomegalovirus infections.